Does Ngo Microfinance Alleviate Poverty In Pakistan? A Quasi-Experimental Approach - Rossazana, Ab-Rahim; Saif-Ul-Mujahid, Shah (Faculty of Economics and Business, UNIMAS, 2019)
Poverty is a global problem and Pakistan is not an exception wherein 37.9 % of the population lives in poverty. It is interesting to highlight due to the lack of government resources in Pakistan, non-governmental organizations (NGOs) microfinance institutions are playing main role in poverty alleviation of the rural areas of Pakistan. This paper aims to investigate the role of NGO microfinance in breaking the vicious cycle of poverty of the poor in Pakistan. Statistical Package for Social Sciences (SPSS) is used to analyse the data obtained from 465 respondents using quasi- experimental approach. The results reveal positive impact on the borrower’s income and consumption while negative impact for saving and assets. Overall, microfinance has improved the well-being of the borrowers.